Damage accrual and mortality over long-term follow-up in 300 patients with systemic lupus erythematosus in a multi-ethnic British cohort. (3rd August 2019) - Segura, Beatriz Tejera; Bernstein, Brett Sydney; McDonnell, Thomas; Wincup, Chris; M Ripoll, Vera; Giles, Ian; Isenberg, David; Rahman, Anisur
Abstract: Objective: Damage in patients with systemic lupus erythematosus is irreversible change in organs due to disease activity, concomitant disease or medication side-effects. It is measured using the Systemic Lupus International Collaborative Clinics Damage Index (SDI) and is associated with increased mortality. Previous reports have suggested associations between damage accrual and various ethnic, disease and treatment factors, but there is a dearth of long-term follow-up data from large multi-ethnic cohorts. We describe a study of damage and mortality in 300 patients from London, UK followed for up to 40 years. Methods: We carried out retrospective analysis of medical records and SDI scores of 300 patients followed for up to 40 years (median 13.3 years). Characteristics of the groups who did and did not develop damage and those who died or survived to the end of follow-up were compared using univariable and multivariable analysis. Kaplan-Meier analysis was used to analyse factors affecting mortality and accrual of damage. Results: Damage developed in 231/300 (77%) of patients. There was a linear accrual of damage over 40 years follow-up. Factors associated with damage were African/Caribbean ethnicity, renal and cerebral involvement, early use of high-dose corticosteroids or immunosuppressants, anti-RNP and antiphospholipid antibodies. Damage was strongly associated with mortality. Of 87 patients who died, 93% had damage compared with 70% of survivors ( P < 0.001). Conclusion: Development of damage is strongly associated with increased mortality. We identified groups at increased risk of developing damage, including those treated with high-dose steroids and immunosuppressants within the first two years.